AN ANALYSIS OF AUTHENTIC MATERIAL USED IN TEACHING ENGLISH AT SD PURI ASAH DASAR AVESIENA GREEN SCHOOL MALANG - Primadona., Yuhalisana; Prastiyowati, Santi (University of Muhammadiyah Malang, 2018)
Authentic material is a material which is used by the purpose to imitate the real-world situations. In addition, the use of authentic material is expected to bring the learners into direct contact with a reality so the students will interest during the learning process. However, the objectives of the research were to investigate kinds of authentic material, to explore the implementation of authentic material, to find out the problem faced by the Englishteacher in using the authentic material of SD PuriAsah Dasar Avesiena Green School Malang. Descriptive qualitative research design was used in this study. The techniques in collecting the data were observation and unstructured interview while field notes and interview guide were used as the instruments. The subject of this research was an English teacher of SD PuriAsah Dasar Avesiena Green School Malang. The result of the research showed that there were forty-eight authentic materials were used in five times observations. The researcher classified those varieties of authentic materials into three kinds of authentic materials: by those forty-eight authentic materials, only one referred to Authentic Visual Material, two referred to Authentic Printed Material, and the rest forty-five referred to Realia which meant it was the most favorable Authentic Material used by the English teacher. In using the authentic material, the teacher usually conducted an outdoor class activity to find out the real object related to the topic. By seeing and holding the real thing, it made the students interested and experienced the real situation. In this case, the problem faced by the teacher was in finding the authentic material which adjusted the students’ grade and topic.